Investment in Housing in the United States : A Portfolio Approach; The Possible Effects of Changes in Tax Policy - Andersson, Krister (IMF Working Papers; Working Paper, 1990)
It is well known that the preferential tax treatment of housing induces an inefficient allocation of saving and investment. This paper analyzes, in a portfolio framework, how eliminating the deductibility of mortgage interest payments for federal income tax purposes might affect investment in housing. Expected rate of return and risk is estimated for three assets, bonds, housing, and stocks. The possibility that assets are imperfect substitutes is explicitly recognized in one section of the paper. The model suggests that the share of housing is likely to decrease by 4 to 9 percentage points if mortgage interest payments are not deductible. This may call for careful phasing of the change in policy.